In Vivo Monitoring of Transcriptional Activity During Metabolic Transition Using a Bioluminescent Reporter in Yeast - Cubillos-Riffo, F; Quintrel-Poblete, P; Benavides-Parra, J (MyJoVE Corporation, 2025)
Sequential sugar consumption, from a preferred sugar source to a less preferred one, represents a critical metabolic adaptation in yeast, which is particularly relevant for survival in fluctuating environments such as those found in beer fermentation. However, sugar transitions are an environmental variable that is challenging to predict and detect, impacting the outcome of beer fermentations. This protocol describes an in vivo system to monitor transcriptional activation associated with the glucose-to-maltose metabolic shift in Saccharomyces eubayanus that applies to different wild Saccharomyces yeast strains. The system employs an episomal bioluminescent transcriptional reporter for maltose metabolism, focusing on MAL32, since it provides a good readout for metabolic shifts, as studied in S. cerevisiae. For this, yeast strains were transformed with plasmids containing the MAL32 regulatory region from S. eubayanus, controlling the expression of a gene encoding for a destabilized version of firefly luciferase1, and a hygromycin resistance gene used exclusively during transformation to ensure plasmid acquisition. Following selection, transformed yeast cells can be cultured under non-selective conditions, as the episomal plasmid remains stable in culture conditions for up to 7 days. This system was validated under a complex sugar environment in microfermentation assays, confirming the effectiveness of the luciferase reporter in informing metabolic transitions. Samples were collected regularly and analyzed with a luminometer, providing continuous insights into yeast responses. While broadly applicable, this protocol is particularly valuable for assessing yeast performance under fermentation conditions, where metabolic changes pose a significant challenge. Additionally, this methodology can be adapted by selecting alternative promoters to explore a broader range of responses to environmental changes, allowing characterization as well as optimization of wild yeast strains for diverse industrial applications. © 2025 JoVE Journal of Visualized Experiments.